2013
DOI: 10.1161/strokeaha.113.001300
|View full text |Cite
|
Sign up to set email alerts
|

Can Hospital Discharge Databases Be Used to Follow Ischemic Stroke Incidence?

Abstract: Background and Purpose-Because acute ischemic strokes (ISs) are mainly hospitalized, hospital discharge data could be used to routinely follow their incidence management. We aimed to assess sensitivity and positive predictive value of the French hospital discharge database (HDD) to identify patients with acute IS using a prospective and exhaustive cohort (AVC69) of acute IS cases. Methods-A selection algorithm based on IS diagnosis coded with the International Classification of Diseases and cerebral imaging c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 25 publications
4
40
2
2
Order By: Relevance
“…Diagnostic coding for stroke has a high positive predictive value when compared with gold-standard clinical neurologist diagnosis. [22][23][24] Although diagnostic misclassification may therefore affect point incidence estimates of TIA, it is much less likely to influence our analysis of trends over time in stroke risk after TIA, or TIA rates, particularly because the same coding system was used for the study period. Notably, the yearly downward trend in the risk of stroke risk was still observed when restricted to patients receiving brain imaging during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic coding for stroke has a high positive predictive value when compared with gold-standard clinical neurologist diagnosis. [22][23][24] Although diagnostic misclassification may therefore affect point incidence estimates of TIA, it is much less likely to influence our analysis of trends over time in stroke risk after TIA, or TIA rates, particularly because the same coding system was used for the study period. Notably, the yearly downward trend in the risk of stroke risk was still observed when restricted to patients receiving brain imaging during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…11 In that study, the overall sensitivity of the French HDD was higher (77%), whereas the positive predictive value was lower (69%) than the one reported by Haesebaert et al 10 Furthermore, in the same study, 10 sensitivity and positive predictive values were heterogeneous across stroke types and were higher for intracerebral hemorrhage as suggested by several previous studies.…”
Section: Sacco Et Al Stroke Tracked By Administrative Coding Datamentioning
confidence: 56%
“…For this reason, the concordance between administrative coding data and medical records has been scrutinized in different settings. 8,9 In the current issue of Stroke, Haesebaert et al 10 reported the results of their study designed to help us understand whether concern about the reliability of administrative coding data in stroke research is ill placed or whether such concern is justified or whether the answer lies somewhere in between the 2 poles. The study assessed the accuracy of the French hospital discharge database (HDD) to identify subjects with acute ischemic stroke.…”
Section: Administrative Coding Data: Advantages and Pitfallsmentioning
confidence: 99%
See 2 more Smart Citations